2020
DOI: 10.34115/basrv4n3-046
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação ambiental por enteroparasitas presentes em areias na Praia do Amor, Distrito de Outeiro, Belém, Pará, Brasil

Abstract: Objetivo: O presente trabalho objetivou analisar a qualidade da areia de uma praia pública, no distrito de Outeiro, em Belém do Pará, quanto à presença de formas parasitológicas. Materiais e métodos: Foram coletadas amostras de areias em pontos específicos de zonas distintas provenientes da Praia do Amor, sendo analisadas individualmente pelas técnicas de Hoffman e de Rugai. Resultados: A realização dos métodos parasitológicos permitiu verificar a presença de parasitas. No método de Hoffman foram encontrados o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
3
0
0
2
Order By: Relevance
“…Other studies conducted in soil from beaches in Brazil reported a low prevalence of parasites in these samples 6,10,17,18 , in accordance with our results. However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other studies conducted in soil from beaches in Brazil reported a low prevalence of parasites in these samples 6,10,17,18 , in accordance with our results. However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 .…”
Section: Discussionsupporting
confidence: 93%
“…Other studies conducted in soil from beaches in Brazil reported a low prevalence of parasites in these samples 6,10,17,18 , in accordance with our results. However, the data about parasitic contamination of beaches are limited in the Northern region of Brazil 17 . In this way, a parasitological analysis performed at the public parks onshore of beaches from Rio Grande do Sul showed 8.3% (10/120) of positivity in soil samples using the Caldwell & Caldwell's technique adapted by Pessoa and Martins (1988) 18 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A falta de tratamento, falta de higienização e a ausência de saneamento básico adequado são alguns desses fatores. Logo, há a necessidade de se realizar ações preventivas para melhorar a qualidade da água do mar, garantindo assim, uma melhor segurança desses ambientes (da Silva et al, 2022;Silva et al, 2020).…”
Section: Introductionunclassified
“…Por meio de contato social e da comercialização, que ajuda no crescimento econômico da região, as ações antropológicas geradas podem acometer crianças e adultos que frequentam esse local, sendo necessário realizar ações preventivas para uma melhor qualidade das areias das praias, para que se possa garantir uma melhor segurança e uma boa qualidade desses ambientes (Silva et al, 2020).…”
Section: Introductionunclassified